IMPLICATIONS OF POLITICAL PARTY RECALL RIGHTS TOWARD DPRD MEMBERSHIP - Aulia Rahman (Faculty of Law, University of Muhammadiyah Malang, 2019)
The concept of recall hegemony to DPRD members to their roles as people's representatives who are representatives of political parties and constituents, can influence the work and performance of DPRD members. Recall rights by political parties can limit the political rights of council members, while shifting people's sovereignty to the sovereignty of political parties. recall procedures for members of the DPRD either through direct political parties or public complaints to the Council's Honorary Board remain through the mechanism of political party decisions. However, there is no legal legitimacy for DPRD members to make legal remedies against recall and guarantee of return of rights if it is proven that it does not fulfill the reason for recall.